Applications behind biochemical wood degradation by Xylophagous fungi: brown and white rot - Mena-Morales, Catalina (2022)
There are different biotic factors that capable of degrading wood, among them xylophagous fungi. Amid the main types of these fungi are those that cause white rot and brown rot. These fungi can be classified according to growth substrate preferences and, wood decomposition patterns. While white rot fungi degrade wood through enzymatic hydrolysis, brown rot fungi follow a two-step degrading process involving lignin-modifying reactive oxygen species derived from Fenton reaction, followed by specialized enzymes that hydrolyze cellulose and hemicellulose. Both types of rot fungi have remarkable biotechnological applications regarding bioremediation. Among the principal applications are waste management, chemical degradation of environmentally persistent compounds, metal detox and others.